Paradoxes of Emancipation (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
This paper relates the concepts of servitude, censorship and emancipation, the point of contact between them being the idea of the necessary consent of the subject and his paradoxical wish not to be free. Étienne de la Boétie, in the middle of the sixteenth century, called it “voluntary servitude”, and claimed that the master’s supremacy does not lie in his power, but in the legitimacy conferred on it by the consent of the servant. During the seventeenth century, the censorship of the Holy Office took the place of the master and regulated free thought and the editing of books. Baltasar Gracián was one writer who confronted this difficulty with ingenuity. A century later, the ideal of emancipation reverts to Étienne de La Boétie’s proposal in the sense of pointing out that the cause of not abandoning the old doctrinal tutelage does not ascribe to an external reality. One response to this paradox was the collective project of the Encyclopédie, led by Denis Diderot.